The contributions of Frederick Winslow Taylor, Henri Fayol, and Max Weber to the development of administrative science - Nurkia A. Djuhaepa; Hasnawati Uloli; Cahya Nakila; Natasya Putri Adam; Siti Hariyanti Mustapa; Alexander Husain Badjuka (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the contributions of Frederick Winslow Taylor, Henri Fayol, and Max Weber to the development of administrative science. The method used is a qualitative approach with library research by collecting data from books, scientific journals, and the original works of these scholars. The results show that Taylor contributed through the concept of Scientific Management, which emphasizes work efficiency, standardized procedures, and labor productivity. Fayol contributed through general administrative theory with five management functions and fourteen administrative principles that became the foundation of modern organizational management. Weber contributed through the theory of rational-legal bureaucracy, emphasizing hierarchy, formal rules, professionalism, and competency-based administrative systems. These three figures played a major role in shaping the foundations of modern administrative science. Although some of their ideas have been criticized as rigid and mechanistic, their basic concepts remain relevant in contemporary organizational practices. This study concludes that the thoughts of Taylor, Fayol, and Weber continue to be important references in the development of public and business administration in the modern era.